Antiretroviral activity of protease inhibitors against Toxoplasma gondii - Monzote, Lianet; Rodríguez, Marta; Alfonso, Yenisey; Cox, Raymundo (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
The introduction of highly active antiretroviral therapy (HAART) has caused a marked reduction in the occurrence and severity of parasitic infections, including the toxoplasmic encephalitis (TE). These changes have been attributed to the restoration of cell-mediated immunity. This study was developed to examine the activity of six antiretroviral protease inhibitors (API) on Toxoplasma gondii tachyzoites. The six API showed anti-Toxoplasma activity, with IC50 value between 1.4 and 6.6 µg/mL. Further studies at the molecular level should be performed to clarify if the use of API could be beneficial or not for AIDS patients with TE.